Kazakhstan: Assessment of Renewable Energy Support and a Green Economy - BESPALYY, Sergey (Journal of Environmental Management and Tourism, 2021)
The growth of renewable energy sources (RES) shows the desire of the government of Kazakhstan to meet challenges that affect the welfare and development of the state. National targets, government programs, policies influence renewable energy strategies. In the future, renewable energy technologies will act as sources of a green economy and sustainable economic growth. The state policy in the field of energy in Kazakhstan is aimed at improving the conditions for the development and support of renewable energy sources, amendments are being made to provide for the holding of auctions for new RES projects, which replaces the previously existing system of fixed tariffs. It is expected that the costs of traditional power plants for the purchase of renewable energy will skyrocket, provided that the goals in the field of renewable generation are achieved. This article provides an assessment of international experience in supporting renewable energy sources, as well as analyzes the current situation in the development of renewable energy in Kazakhstan and the impact on sustainable development and popularization of the «green» economy. The study shows that by supporting the development of renewable energy sources, economic growth is possible, which is achieved in an environmentally sustainable way.